A Chronic Implant to Record Electroretinogram, Visual Evoked Potentials and Oscillatory Potentials in Awake, Freely Moving Rats for Pharmacological Studies. Issue 3 (2004) - Guarino, Irene; Loizzo, Stefano; Lopez, Luisa; Fadda, Antonello; Loizzo, Alberto
Abstract : Electroretinogram (ERG), widely used to study the pharmacological effects of drugs in animal models (e.g., diabetic retinopathy), is usually recorded in anesthetized rats. We report here a novel simple method to obtain chronic implantation of electrodes for simultaneous recording at the retinal and cortical levels in freely moving, unanesthetized animals. We recorded cortical (VEPs) and retinal (ERGs) responses evoked by light (flash) stimuli in awake rats and compared the results in the same rats anesthetized with urethane (0.6 mg/kg) before and after the monocular administration of scopolamine methyl bromide (1 solution). We also compared the retinal responses with those derived from a classic acute corneal electrode. Anesthesia induced consistent changes of several VEP and ERG parameters like an increase of both latency and amplitude. In particular, the analysis of the variation of latency, amplitude, and spectral content of rapid oscillatory potentials could be important for a functional evaluation of the visual system in unanesthetized versus anesthetized animals.